A call to action: a stakeholder analysis of green logistics practices - Prataviera, Lorenzo Bruno; Creazza, Alessandro; Perotti, Sara (Emerald, 2023)
Purpose – There is a growing body of literature discussing the green logistics practices (GLPs) that companies could introduce to reduce the logistics environmental impact. Current approaches also identify several influencing factors within firms that could serve as barriers to, or enablers of, GLPs. However, less is known about the role of extra-firm stakeholders, even though these are crucial to operationalizing green logistics effectively. This study merges current theoretical understanding with empirical evidence to provide a detailed stakeholder analysis of GLPs. Design/methodology/approach – Using stakeholder theory as a theoretical lens, we aimed at offering a mid-range contribution by conducting multiple embedded case studies examining Italian logistics service providers and shippers. GLPs and the related influencing factors were examined as sub-units of analysis within broader companies’ environmental sustainability strategies. Findings – We identified cascading effects among factors influencing the adoption of GLPs (e.g., key economic factors are affected by external factors which also influence organizational and collaboration factors). These effects are moderated by interdependencies between primary and secondary stakeholders, and the study highlights the prominent involvement of secondary stakeholders, such as final consumers. Originality/value – Our paper contributes to better understanding how and why companies adopt GLPs, emphasizing the wide set of stakeholders involved and illustrating how different stakeholders impact on GLPs adoption by affecting a set of influencing factors. By combining insights from the available literature with contemporary empirical data, we emphasize how Logistics Service Providers and shippers can no longer address the adoption of GLPs as “focal companies”, but only as part of a “focal network of interconnected stakeholders”, all of them influencing GLPs adoption.
Keywords: logistics; green practices; environmental sustainability; stakeholder theory; case research